Visualization of Volcanic Landform with Augmented Reality - Rakhmat Jaya Lahay; Indrawan Indrawan; Mohamad Fachri Bokingo; Merlin Lauhi; Puspita Rahmat (JURNAL GEOGRAFI, 2023)
Visualization of volcanic landforms with digital elevation model (DEM) data on the GIS desktop computer has limitations regarding access to the software display function and its use outside the room. This obstacle can be overcome by combining GIS and mobile augmented Reality. However, using digital elevation model data and satellite imagery in augmented reality software has not been widely explored. This study shows a practical way of integrating geospatial data with mobile augmented reality software. This research aims to create an augmented reality prototype to visualize virtual volcano objects. DEM data and satellite imagery create 3-dimensional (3D) objects and provide texture characteristics of volcanic landform objects. Visualization of volcanic landforms is done through an augmented reality (AR) application prototype on an Android smartphone. The experimental results show that augmented reality technology effortlessly combines DEM data and land features from satellite imagery. Evaluation of a smartphone device's manufacturing and installation stages shows results with a "successful" status. Through follow-up testing nine times, the AR prototype showed positive performance in all aspects of distance, angle, and lighting. The final test scenario in the form of responses regarding the application from other users obtained an average value of the "Good" category of 92.8%. In conclusion, these results indicate that the system built can be used in learning. However, further research requires more diverse test scenarios to see how far this application prototype can be used in various conditions. Keywords: Digital Elevation Model, GIS, Augmented Realit, 3D Visualization